ARCHITECTURE ACCORDING TO PHILOSOPHY OF CROSSING (AL – UOBOR) - Ahmed Talib Hameed Haddad (Iraqi Journal of Architecture and Planning, 2017)
This research aims to discuss the concept of architecture historically according to intellectual rules of Dr. Ali Al-Jabri philosophy as it is the basic model from which the concept of intellectual concepts, including the concept of the crossing term (al – uobor), which is the dynamic engine of the Jabri philosophical model, to formulate the research vision of architecture according to the philosophy of (al – uobor). The general problem of research in the study of architecture as a cultural phenomenon with intellectual roots in philosophers. The research problem was formed in the activation of local philosophical frameworks and models to interpret architecture as a cultural phenomenon with a cultural dimension that has its specificity within the Arab Islamic culture and using the intellectual models of local philosophers such as Dr. Jabri, This philosophical model, especially the philosophy of (al – uobor), will shed light on the development of architecture as a human product that reflects the human civilization in its passage through obstacles throughout history. To develop conclusions and recommendations that pave the way for the possibility of building a general outlook for the future explaining the phenomenon of architecture as a cultural act through the ideas of one of the most prominent contemporary Iraqi philosophers.